Síntese e propriedades fotocatalíticas do titanato de bismuto obtido pela rota dos complexos oxidantes de peróxido - Nogueira, André Esteves (Universidade Federal de São Carlos, 2014)
The welfare of the population and technological progress of our society largely depend on the development and the intensive use of synthetic materials, generating a large amount of residual chemicals and high energy consumption. Therefore, the need for development of synthesis routes that are more efficient, economic and environmentally sustainable, both for obtaining new materials as well as for improvement of those traditionally used by the productive sector, has grown in importance. Therefore, the study aimed to understand and extend the use of the oxidant peroxide method (OPM), as a new synthesis route for obtaining bismuth titanate with the sillenite (Bi12TiO20) and perovskite (Bi4Ti3O12) phase. In addition, we studied the influence of defects formed in the structure by the introduction of dopants such as niobium, lanthanum, and lead. These changes were made to obtain materials with improved structural and optical properties for use in the photodegradation process of the organic dye rhodamine B (RhB) under ultraviolet and visible radiation. Through obtaining the amorphous precipitate by the OPM route we observed the formation of spheres of bismuth oxide (Bi2O3) with titanium dioxide (TiO2) nanoparticles with surface peroxo groups that were identified as mainly responsible for the high reactivity of the powders obtained by this synthesis method. The photocatalytic properties of all materials were evaluated by the discoloration of RhB solution under UV and visible irradiation, where the bismuth titanate obtained by the OPM route showed higher photocatalytic activity than the commercial TiO2. Obtaining bismuth titanate calcined at different temperatures allowed the understanding of the effects of crystallinity on the photocatalytic activity. Furthermore, it was observed that the insertion of different ions in the bismuth titanate (Bi12TiO20) structure modified the band gap energy in different ways, which consequently altered the photocatalytic activities of the materials, showing the dependence of the redox potential of the conduction and valence band in the photocatalysis process.
Photocatalytic properties of bismuth titanate synthesized by the oxidant peroxide method
Keywords: Fotocatálise; Titanato de bismuto; Síntese; Rodamina B; Peroxo-complexo; CIENCIAS EXATAS E DA TERRA::QUIMICA